Community Mental Health Services and Research Clinic (KP2KJM) Muhammadiyah University of East Kalimantan - Mukhripah Damaiyanti; Ghozali MH; Dwi Rahmah Fitriani; Ramdhany Ismahmudi; Yuliani Winarti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Mental health disorders will interfere the overall health of a person, so families and communities needs to increase the knowledge of families and community members in determining the condition of mental disorders, as well as how to intervene and implement mental disorder management. There are some services for it, namely the mental health consultation service program, modality therapy, client home visits, health education for the community, and mental health cadres. The results in the change of percentage level of family knowledge after given the actions are as follows: moderate category increases from 35.7% to 46.03%, the good category increases from 23.02% to 33.86%, while the poor category decreases from 41.27% to only 20.11%. It is currently preparing to collaborate with doctors and Healthcare and Social Security Agency (Badan Penyelenggara Jaminan Sosial or BPJS) as the first-level health facilities and pharmacy services that are open to the public. Based on the results of research conducted, it shows that the program implemented can increase knowledge of mental health services in the community.